Pengaruh Pengendalian Internal Dan Good Corporate Governance (GCG) Terhadap Pencegahan Fraud Di JII (Studi Empiris Pada Perusahaan Yang Terdaftar Di Jii 30 Tahun 2015-2021) - Desilis Kartika; Erma Setiawati (Economics and Digital Business Review, 2024)
This study aims to obtain empirical evidence and to analyze the effect of corporate governance’s mechanism such as internal control, institutional ownership, managerial ownership, and independent board of commissioners on likelihood of fraudulent financial reporting. This study uses secondary data from the company’s annual report for 2015-2021. The sample in this study is a company listed on the Jakarta Islamic Index 30 (JII 30) whoch has consistently entered for the las ten years. According to the certain criteria as many 35 sample for the last seven years. The analysis used in this study is logistic regression analysis. The result showed that all of corporate governance’s mechanism such as internal control, institutional ownership, managerial ownership, and board of commissioners have no significant effect on likelihood of fraudulent financial reporting.